Outcomes of Women With High-Grade and Low-Grade Advanced-Stage Serous Epithelial Ovarian Cancer. Issue 3 (March 2017) - Gockley, Allison; Melamed, Alexander; Bregar, Amy J.; Clemmer, Joel T.; Birrer, Michael; Schorge, John O.; del Carmen, Marcela G.; Rauh-Hain, J. Alejandro
Abstract : OBJECTIVE: To compare outcomes of women with advanced-stage low-grade serous ovarian cancer and high-grade serous ovarian cancer and identify factors associated with survival among patients with advanced-stage low-grade serous ovarian cancer. METHODS: A retrospective study of patients diagnosed with grade 1 or 3, advanced-stage (stage IIIC and IV) serous ovarian cancer between 2003 and 2011 was undertaken using the National Cancer Database, a large administrative database. The effect of grade on survival was analyzed using the Kaplan-Meier method. Factors predictive of outcome were compared using the Cox proportional hazards model. Among women with low-grade serous ovarian cancer, propensity score matching was used to compare all-cause mortality among similar women who underwent chemotherapy and lymph node dissection and those who did not. RESULTS: A total of 16, 854 (95.7%) patients with high-grade serous ovarian cancer and 755 (4.3%) patients with low-grade serous ovarian cancer were identified. Median overall survival was 40.7 months among high-grade patients and 90.8 months among women with low-grade tumors ( P <.001). Among patients with low-grade serous ovarian cancer in the propensity score-matched cohort, the median overall survival was 88.2 months among the 140 patients who received chemotherapy and 95.9 months among the 140 who did not receive chemotherapy ( P =.7). Conversely, in the lymph node dissection propensity-matched cohort, median overall survival was 106.5 months among the 202 patients who underwent lymph node dissection and 58 months among the 202 who did not ( P <.001). CONCLUSION: When compared with high-grade serous ovarian cancer, low-grade serous ovarian cancer is associated with improved survival. In patients with advanced-stage low-grade serous ovarian cancer, lymphadenectomy but not adjuvant chemotherapy was associated with improved survival. Abstract : In advanced serous ovarian cancer, low-grade tumors have a better prognosis than high-grade tumors; in low-grade tumors, lymphadenectomy, but not chemotherapy, is associated with improved survival.